THE ANTECEDENTS OF ONLINE MARKETPLACE ADOPTION INTENTION AMONG FOOD MSE’S OWNERS IN INDONESIA: A CONCEPTUAL PAPER - Budiarti, Astra Prima; Abu Karim, Rizuwan; Hanapiyah, Zulkefli Muhamad; Iskandar, Ainaa Idayu; Abas, Norazira Mohd (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
Improving the willingness of Food Micro and Small Enterprises (MSEs) owners to utilise online marketplaces, with the objective of boosting local product market penetration and enhancing business efficiency, may substantially contribute economic development in Indonesia. This study aims to develop a framework based on a literature review to explain the factors affecting the online marketplace adoption intentions of Food MSEs owners in Indonesia. A comprehensive literature review on adoption intention was performed to propose a conceptual framework illustrating the relationships among technology, organisation, and environmental determinants, which subsequently affect the intention to adopt online marketplaces. The proposed framework is applicable to Food MSEs in Indonesia and may also be relevant to other Food MSEs sectors in rural business areas. The implementation of this conceptual model would enable governments to better understand the effects of the proposed factors on the intention to adopt online marketplaces among Food MSEs, thus aiding in the formulation of appropriate policies.